2019
DOI: 10.1103/physreva.99.032704
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the fully differential cross sections for single ionization of He in collisions with 75-keV protons

Abstract: We present a theoretical investigation of the single ionization of He in collisions with H + projectile ions at 75-keV impact energy. Using the frameworks of the independent-electron model and the impact parameter picture, fully differential cross sections (FDCS) are evaluated in the continuum distorted-wave with eikonal initial-state approximation (CDW-EIS). Comparisons are made to the recent measurements of Schulz et al. [Phys. Rev. A 73, 062704 (2006)] and Arthanayaka et al. [J. Phys. B: At. Mol. Opt. Phys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In numerous follow-up experiments, similar projectile coherence effects on the cross sections were observed [20][21][22][23][24][25][26][27][28][29][30] (for a review, see [31]). Furthermore, the interpretation of the experimental data was supported by several theoretical studies, e.g., [32][33][34][35][36].…”
Section: Introductionsupporting
confidence: 56%
“…In numerous follow-up experiments, similar projectile coherence effects on the cross sections were observed [20][21][22][23][24][25][26][27][28][29][30] (for a review, see [31]). Furthermore, the interpretation of the experimental data was supported by several theoretical studies, e.g., [32][33][34][35][36].…”
Section: Introductionsupporting
confidence: 56%
“…From the above, it follows that the optimal choice for Q, which provides the most accurate account of the proton-electron interaction achievable within our approach, is the admissible value closest to K 0 . Above such upper bound Q 0 , the p − e potential can no longer be considered as a perturbation (compared with E e f f ), thus resulting in the very poor convergence of the FDCS as more terms are included in the Sturmian representation (21).…”
Section: Matrix Equation For the Coefficients C Nmentioning
confidence: 99%
“…At a lower impact energy, the absolute FDCS of singly ionizing 75-keV p − He collisions have been measured in various kinematical regimes [13]. For these FDCS, theoretical predictions were obtained based upon the well-known continuum distortedwave-eikonal initial-state (CDW-EIS) model [14,15], (a) including the projectile and residual target ion interaction (CDW-EIS PI) [16]; (b) the two-Coulomb final wave (2C) + the initial Coulomb projectile wave [17]; (c) the three-Coulomb wave (3C) model [18]; (d) the modified Coulomb-Born approximation (MCB-PI) [19]; (e) the continuum correlated wave model including the interaction between the projectile and the residual target ion (CCW-PT) [20]; (f) including the projectile target core (NN) interaction model convolved with experimental resolution (CDW-EIS NN) [21]. Despite the sophistication of the latest approaches, none of them has managed to reach complete agreement with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Strictly, equation (4) holds exactly in an ideal experiment where two momenta are determined accurately, and K and k are well defined by | ( )| . Note that the expression of the EFDCS depends on the two momenta selected [40,43]. When k e and p r are selected (corresponding to method (c) in section 1), K f can take various values.…”
Section: Effective Fully Differential Cross-sectionmentioning
confidence: 99%
“…The analysis of Kouzakov [41] is valid when the fluctuation of relative velocity between the projectile and the target is much smaller than the average velocity (see appendix A of [43]), which is usually realized in collision experiments. Recently, Gassert et al [17] reported FDCS data for a 1 MeV proton + He collision.…”
Section: Introductionmentioning
confidence: 99%